The glassy behaviour of poorly crystalline Fe2O3 nanorods obtained by thermal decomposition of ferrous oxalate. (27th February 2015) - Perovic, M; Kusigerski, V; Mrakovic, A; Spasojevic, V; Blanusa, J; Nikolic, V; Schneeweiss, O; David, B; Pizúrová, N
Abstract: Nanorod ferrous oxalate dihydrate (FeC2 O4  × 2H2 O) which had been synthesized by the microemulsion method, was used as a precursor in the thermal decomposition process performed in air atmosphere. The formation of nanocrystalline hematite as the final product was preceded by the appearence of an intermediate product. Comprehensive study comprising several complementary techniques (x-ray diffraction, transmission electron microscopy, selected area electron diffraction, thermogravimetric/differential thermal analyses and SQUID magnetometry) confirmed that the intermediate product corresponds to the poorly crystalline Fe2 O3 . Due to the specific nanorod shape and poorly crystalline structure, the investigated Fe2 O3 showed high coercive field value of at Special attention in this study was devoted to the peculiar magnetic properties of poorly crystalline Fe2 O3, which were thoroughly investigated by employing sophisticated experimental procedures such as relaxation of thermoremanent magnetization for different cooling fields, zero field and field cooled memory effects as well as aging experiments for different waiting times. At low temperatures and weak applied magnetic fields, the investigated system behaves similarly to spin glasses, manifesting slow, collective relaxation dynamics of magnetic moments through memory, rejuvenation and aging effects.